Resistance to Radiotherapy in Cancer - Almaz A. Akhunzianov; Elvira V. Rozhina; Yuliya V. Filina; Albert A. Rizvanov; Regina R. Miftakhova (Diseases)
Radiation therapy or radiotherapy is a medical treatment that uses high doses of ionizing radiation to eliminate cancer cells and shrink tumors. It works by targeting the DNA within the tumor cells restricting their proliferation. Radiotherapy has been used for treating cancer for more than 100 years. Along with surgery and chemotherapy, it is one of the three main and most common approaches used in cancer therapy. Nowadays, radiotherapy has become a standard treatment option for a wide range of cancers around the world, including lung, breast, cervical, and colorectal cancers. Around 50% of all patients will require radiotherapy, 60% of whom are treated with curative intent. Moreover, it is commonly used for palliative treatment. Radiotherapy provides 5-year local control and overall survival benefit in 10.4% and 2.4% of all cancer patients, respectively. The highest local control benefit is reported for cervical (33%), head and neck (32%), and prostate (26%) cancers. But no benefit is observed in pancreas, ovary, liver, kidney, and colon cancers. Such relatively low efficiency is related to the development of radiation resistance, which results in cancer recurrence, metastatic dissemination, and poor prognosis. The identification of radioresistance biomarkers allows for improving the treatment outcome. These biomarkers mainly include proteins involved in metabolism and cell signaling pathways.